Confocal Microscopy-Based Estimation of Parameters for Computational Modeling of Electrical Conduction in the Normal and Infarcted Heart - Greiner, Joachim; Sankarankutty, Aparna C.; Seemann, Gunnar; Seidel, Thomas; Sachse, Frank B. (Frontiers in Physiology, 2018)
Computational modeling is an important tool to advance our knowledge on cardiac diseases and their underlying mechanisms. Computational models of conduction in cardiac tissues require identification of parameters. Our knowledge on these parameters is limited, especially for diseased tissues. Here, we assessed and quantified parameters for computational modeling of conduction in cardiac tissues. We used a rabbit model of myocardial infarction (MI) and an imaging-based approach to derive the parameters. Left ventricular tissue samples were obtained from fixed control hearts (animals: 5) and infarcted hearts (animals: 6) within 200 µm (region 1), 250 to 750 µm (region 2) and 1000 to 1250 µm (region 3) of the MI border. We assessed extracellular space, fibroblasts, smooth muscle cells, nuclei and gap junctions by a multi-label staining protocol. With confocal microscopy we acquired three-dimensional (3D) image stacks with a voxel size of 200 200 200nm. Image segmentation yielded 3D reconstructions of tissue microstructure, which were used to numerically derive extracellular conductivity tensors. Volume fractions of myocyte, extracellular, interlaminar cleft, vessel and fibroblast domains in control were (in %) 65.03 3.60, 24.68 3.05, 3.95 4.84, 7.71 2.15 and 2.48 1.11, respectively. Volume fractions in regions 1 and 2 were different for myocyte, myofibroblast, vessel and extracellular domains. Fibrosis, defined as increase in fibrotic tissue constituents, was (in %) 21.21 1.73, 16.90 9.86 and 3.58 8.64 in MI regions 1, 2 and 3, respectively. For control tissues, image-based computation of longitudinal, transverse and normal extracellular conductivity yielded (in S/m) 0.36 0.11, 0.17 0.07 and 0.1 0.06, respectively. Conductivities were markedly increased in regions 1 (+75 %, +171% and +100%), 2 (+53%, +165% and 80%), and 3 (+42%, +141% and +60%). Volume fractions of the extracellular space including interlaminar clefts strongly correlated with conductivities in control and MI hearts. Our study provides novel quantitative data for computational modeling of conduction in normal and MI hearts. Notably, our study introduces comprehensive statistical information on tissue composition and extracellular conductivities on a microscopic scale in the MI border zone. We suggest that the presented data fill a significant gap in modeling parameters.